2003
DOI: 10.1890/1540-9295(2003)001[0412:agitqr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A gentle introduction to quantile regression for ecologists

Abstract: Quantile regression is a way to estimate the conditional quantiles of a response variable distribution in the linear model that provides a more complete view of possible causal relationships between variables in ecological processes. Typically, all the factors that affect ecological processes are not measured and included in the statistical models used to investigate relationships between variables associated with those processes. As a consequence, there may be a weak or no predictive relationship between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
715
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,542 publications
(780 citation statements)
references
References 8 publications
4
715
0
Order By: Relevance
“…Quantile regression can fit a model to portray the change in the 50th (median) or any other quantile of the distribution of distance as a function of time. While the 50th quantile provides a measure of the central trend of the data, the upper quantiles, i.e., the 90th or 95th, can be considered the unconstrained rate of spread [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…Quantile regression can fit a model to portray the change in the 50th (median) or any other quantile of the distribution of distance as a function of time. While the 50th quantile provides a measure of the central trend of the data, the upper quantiles, i.e., the 90th or 95th, can be considered the unconstrained rate of spread [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…In order to get a more complete assessment of how fire size responded to our predictor variables of interest, we used a modelling technique called quantile regression to assess the relationships between fire size distribution and the precipitation, N deposition and biomass variables. Quantile regression (Koenker and Bassett 1978) estimates the effects of explanatory variables for different portions of the distribution of a response variable, rather than just modelling the mean response, and has been shown to be a useful technique for analysing a variety of ecological datasets (Cade and Noon 2003), including identifying relationships between wildfire size and climate variables (Slocum et al 2010). A series of modelling functions is estimated at different levels of t, with t representing the fractions of expected response values (e.g.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Functions can be estimated for a range of t between zero and one, resulting in multiple rates of change (slopes) between an explanatory variable and the response variable, therefore providing a more complete picture of how the distribution of the response is changing given changes in a set of predictor variables. Quantile regression is a semi-parametric modelling technique because no parametric distributional form is assumed for the random error part of the model, whereas a parametric form is assumed for the deterministic part (Cade and Noon 2003). Graphical visualisations of two model variablesfire size and distance to road -suggested that they should be log-transformed before analysis to meet this assumption.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Quantile regression is a robust technique that can provide a good approach to detecting how a species may respond to environmental fluctuations (Eastwood et al 2003). When the distribution of parameters is free and even though part of the limiting factors is used, it can more accurately estimate the responses of a species with respect to habitat variables, especially for the upper quantiles in regression models (Cade and Noon 2003).…”
Section: Introductionmentioning
confidence: 99%